SP7.2.1 Simultaneous intestinal surgery does not increase complication or recurrence rates after complex abdominal wall reconstruction. (28th October 2021) - Wallace, Alison; Garner, Jeffrey
Abstract: Aims: To compare post-operative outcomes in patients undergoing elective complex abdominal wall reconstruction (CAWR) alone vs. CAWR plus simultaneous intestinal surgery. Methods: All patients undergoing elective CAWR over a 10-year period in our unit were identified from a prospectively maintained database and divided into those who had concomitant intestinal surgery (resection, ileoanal-pouch formation, stoma reversal, etc) and those who did not. Simple adhesiolysis, cholecystectomy and gynaecological procedures were not classed as 'intestinal surgery'. Differences between groups were determined using the paired-t test and the (n-1) Chi-squared test. Results: 59 patients underwent elective CAWR, 16 with intestinal surgery and 43 without. The two groups had similar baseline demographics with no significant differences in age, BMI, sex or hernia size. The commonest post-operative complications were pneumonia (33.9%) and wound infections (25.4%) but there were no significant differences in any complication between groups. There was zero 30 and 90 day mortality in either group. The mean operating time in the intestinal group (IG) was significantly longer compared to the CAWR-only group (5.4 +/- 1.3hrs vs 4.1 +/- 1.8hrs, p = <0.05). There was no statistically significant difference between groups in rates of surgical site occurrence (37.5% IG vs 55.81% CAWR-only), mesh infections (0% IG vs 6.98% CAWR-only) or recurrent hernia (6.24% IG vs 9.30% CAWR-only) over a median follow up of 3.0 (0.1-7.8) years. Conclusion: Performing simultaneous intestinal surgery during complex abdominal wall repair is safe and does not increase the risk of recurrence or mesh infections in a specialist abdominal reconstruction unit.